2014
DOI: 10.1142/s0219749914500129
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic tripartite sharing of eight restricted sets of single-qubit operations with two Bell states or a GHZ state

Abstract: Two tripartite schemes with a pair of Bell states and a Greenberger-Horne-Zeilinger (GHZ) state respectively have been proposed recently by Zhang and Cheung for remotely sharing two restricted sets of operations in a deterministic manner [J. Phys. B 44 (2011) 165508]. In this paper, we generalize the schemes with the same quantum channels so that another six restricted sets of operations can be shared deterministically, too. Features about scheme security, sharer symmetry, ful¯llment determinacy and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Shared entanglements are indispensable in QOS [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In all existing QOS schemes, some multi-particle entangled states, such as Bell and GHZ states [25,37], W states [29,31], cluster states [30,32], genuine states [26,38] and so on, have been employed as quantum channels to fulfill QOS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared entanglements are indispensable in QOS [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In all existing QOS schemes, some multi-particle entangled states, such as Bell and GHZ states [25,37], W states [29,31], cluster states [30,32], genuine states [26,38] and so on, have been employed as quantum channels to fulfill QOS.…”
Section: Introductionmentioning
confidence: 99%
“…Shared entanglements are indispensable in QOS [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In all existing QOS schemes, some multi-particle entangled states, such as Bell and GHZ states [25,37], W states [29,31], cluster states [30,32], genuine states [26,38] and so on, have been employed as quantum channels to fulfill QOS. In 2005, Brown et al [39] creatively presented and deeply studied a fivequbit state by means of the computationally tractable entanglement measure developed by themselves and found that it is more highly entangled than a five-qubit GHZ state.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea of quantum operation sharing in a simplest case is that, with shared entanglement and local operations and classical communications (LOCC) the initial performer of a singlequbit operation can assure the operation be finally performed on a remote target's qubit in a agent's site if and only if both agents cooperate [25]. Recently, some QOS schemes have been devised by using different entangled states [25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%